Investigation of mechanical properties of hot mix asphalts with modified binders with SBS, 611 and 701 polymers - Sayedzada, Sayed Enayatullah; Ozdemir, Ahmet Munir; Yalcin, Erkut; Yilmaz, Mehmet (Springer, 2024)
A wide variety of additives are used to improve the performance of hot mix asphalt (HMA). Among these materials, styrene butadiene styrene (SBS) elastomer is one of the most commonly used additives. In this study, in addition to the SBS, the newly produced 711 and 601 elastomers were used as an alternative. Modified binders were prepared by adding three different elastomers in three different ratios (2%, 3%, and 4%) to pure bitumen. The HMA samples were prepared by mixing the modified binders and pure binder with the aggregate pile that is in a certain gradation. Subsequently, the mechanical and fracture properties of these mixture samples were investigated. Marshall stability, resistance to moisture damage (tensile ratio), indirect tensile stiffness modulus (ITSM), and indirect tensile fatigue test were performed on all the prepared mixture samples. In addition, semi-circular HMA samples with two different notch depths, 1 cm, and 2 cm, were obtained and their fracture properties were evaluated with different fracture mechanics approaches. The fracture performance test was evaluated with linear elastic fracture mechanics (LEFM) and elastic-plastic fracture mechanics (EPFM). As a result, fracture toughness and J-integral values were obtained. The results showed that all three elastomers exhibited higher mechanical performance compared to the pure mixture while the highest performances were observed in the mixtures containing 611. When the additives are evaluated among themselves, the ranking is 611, 701, and SBS, respectively. In addition, similar results were obtained according to their fracture performance and it was seen that 701 and 611 elastomers offered better results than SBS.
Keywords: Hot mix asphalt (HMA); Styrene-butadiene-styrene (SBS); Mechanical properties; Semi-circular bending (SCB); J-integral